UNDERSTANDING CORPORATE ENTREPRENEURSHIP IN FAMILY FIRMS: A SYSTEMATIC REVIEW OF ANTECEDENTS, MECHANISMS, AND LONG-TERM IMPACT - Amanda Amelinda; Hastin Umi Anisah; Dian Masita Dewi (Adisam Publisher, 2025)
This study aims to deepen the understanding of Corporate Entrepreneurship (CE) within family firms by systematically reviewing its antecedents, mechanisms, and long term impacts. Family firms possess unique characteristics shaped by family values, identity, governance patterns, and intergenerational goals, which create a distinctive context for the emergence and development of CE. However, existing research remains fragmented, making it difficult to fully capture how CE functions within these organizations. Using the Systematic Literature Review (SLR) method, this study analyzes selected primary studies published between 2006 and 2025 to synthesize evidence on how family related factors influence CE, through what mechanisms entrepreneurial intentions are transformed into innovative actions, and how CE contributes to long term sustainability. The findings show that CE in family firms is driven by family values, identity configurations, socioemotional goals, successor competencies, and stewardship oriented governance. CE operates through cognitive, behavioral, relational, and structural mechanisms that translate entrepreneurial intentions into innovation, strategic renewal, and new venture creation. Furthermore, CE strengthens innovation capability, enhances adaptability, and supports transgenerational continuity. This study contributes to family business literature by integrating diverse insights into a comprehensive conceptual understanding of CE in family firms and offers implications for theory and managerial practice.